Purpuric rash after starting hemodialysis—not the immediate suspect: a case report and literature review - Jiries, George; Vdovich, Olga; Badran, Ashraf; Kruzel-Davila, Etty (Frontiers in Nephrology, 2025)
BackgroundVitamin C deficiency is an underrecognized yet prevalent concern in hemodialysis patients, driven by dietary restrictions, increased oxidative stress, and vitamin losses during dialysis. While supplementation could mitigate deficiency-related complications and reduce inflammation and oxidative damage, clinical implementation remains limited due to concerns about oxalosis and potential pro-oxidative effects.Case presentationWe report the case of a 74-year-old female with End-Stage Kidney Disease (ESKD) secondary to diabetic nephropathy who developed scurvy after prolonged hemodialysis. She presented with unintended weight loss, gingival bleeding, and recurrent pulmonary edema. Physical examination revealed characteristic dermatological findings, including perifollicular erythema predominantly on the lower extremities. Laboratory testing confirmed severe vitamin C deficiency, with serum levels below the detection limit of 4 mg/L, along with hypoalbuminemia and elevated inflammatory markers. Nutritional assessment indicated adherence to standard hemodialysis dietary restrictions, likely exacerbating deficiency.Intervention and outcomesOral vitamin C supplementation resulted in significant clinical improvement, including resolution of dermatological manifestations, cessation of gingival bleeding, improvement in cardiac function, and without recurrence of pulmonary edema episodes, with no adverse effects observed.ConclusionThis case highlights the importance of considering scurvy in hemodialysis patients, particularly those with inflammation and restrictive dietary patterns. It underscores the clinical manifestations of vitamin C deficiency, its potential cardiovascular implications, and the need to revisit supplementation guidelines in this population. The findings support the safe and effective use of vitamin C supplementation in reversing deficiency-related complications while emphasizing the broader consideration of routine vitamin C supplementation in hemodialysis patients, even in the absence of overt clinical manifestations.